Structure and dynamics of the Pacific North Equatorial Subsurface Current - Xiang Li (Nature Portfolio, 2020)
Abstract The North Equatorial Subsurface Current (NESC) has recently been found to flow westward below the North Equatorial Countercurrent in the subsurface layer across the Pacific Ocean. The structure, water mass properties, and the dynamics of the NESC are studied using Argo profiles and geostrophic currents, combined with moored current meter observations. The mean westward geostrophic currents of the NESC has been validated with moored current meter measurements at 4.7° N, 142° E in the far western tropical Pacific Ocean. Sizable seasonal-to-interannual variability of the NESC is indicated by the observations, with strong transports in boreal summer and during La Niña events, whereas weak transports in boreal winter and during El Niño events. The water masses of the NESC appear to be the mixture of the North and South Pacific intermediate waters, with the waters immediately below the thermocline closer to the North than to the South Pacific waters. A simulation using a linear continuously stratified model of ocean circulation suggests that the mean NESC is forced by wind curl through low baroclinic mode responses of the ocean.